Pivotal Role of Anterior Cingulate Cortex in Working Memory after Traumatic Brain Injury in Youth - Cazalis, Fabienne; Babikian, Talin; Giza, Christopher; Copeland, Sarah; Hovda, David; Asarnow, Robert F. (Frontiers in Neurology, 2011)
In this fMRI study, the functions of the Anterior Cingulate Cortex were studied in a group of adolescents who had sustained a moderate to severe Traumatic Brain Injury. A spatial working memory task with varying working memory loads, representing experimental conditions of increasing difficulty, was administered. In a cross-sectional comparison between the patients and a matched control group, patients performed worse than Controls, showing longer reaction times and lower response accuracy on the spatial working memory task. Brain imaging findings suggest a possible double-dissociation: activity of the Anterior Cingulate Cortex in the Traumatic Brain Injury group, but not in the Control group, was associated with task difficulty; conversely, activity of the left Sensorimotor Cortex in the Control group, but not in the TBI group, was correlated with task difficulty. In addition to the main cross-sectional study, a longitudinal study of a group of adolescent patients with moderate to severe Traumatic Brain Injury was done using fMRI and the same spatial working memory task. The patient group was studied at two time points: one time point during the post-acute phase and one time point 12 months later, during the chronic phase. Results indicated that patients' behavioral performance improved over time, suggesting cognitive recovery. Brain imaging findings suggest that, over this 12 month period, patients recruited less of the Anterior Cingulate Cortex and more of the left Sensorimotor Cortex in response to increasing task difficulty. The role of Anterior Cingulate Cortex in executive functions following a moderate to severe brain injury in adolescence is discussed within the context of conflicting models of the Anterior Cingulate Cortex functions in the existing literature.